MOTIF EKSTERNAL KEHADIRAN MAHASISWA PADA MATA KULIAH EVALUASI PEMBELAJARAN - David Firna Setiawan (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
Attendance is one variable that is considered capable of providing a significant positive influence on academic performance. However, the external motives behind student behavior which included attendance were still dominated by awards. This study aims to identify the internal motives of student attendance in learning evaluation courses. The independent variable proposed is the desire to get the best rating in the learning process and attitudes towards regulation. The results showed that the desire to get the best rating in the learning process and attitudes toward regulation could not be used to explain and predict student attendance in learning evaluation courses. Therefor further research should conduct a study of the wider population and propose other independent variables. Although it cannot be used to explain and predict student attendance in learning evaluation lectures, the results of the study still show that students have the desire to get the highest ranking that is quite high in lectures and a positive response to regulation.                                                                                               Keywords: Attendance, external motivation, Learning evaluation